2001
DOI: 10.1113/eph8602135
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the Timing of Indomethacin Treatment in a Model of Synchronized Bone Remodelling in Rats

Abstract: Prostaglandins (PGs) promote both bone resorption and formation in vitro and in vivo. In a synchronised model of bone remodelling, indomethacin, an inhibitor of PG synthesis, given from the start of the sequence, transiently impaired bone resorption. In this study we further explored the involvement of PGs in this model by treating rats with indomethacin (7.5 mg kg _1 day _1 ) for 6 days from the peak of resorption (day 4 after activation in this model) or during reversal (day 6 after activation). In rats trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Recent evidence in a rat model of bone remodelling shows different effects of indomethacin at different time points. 38 These in vitro findings need further study to clarify the relationship between length of exposure to NSAID and the ability of cells to recover from the insult.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent evidence in a rat model of bone remodelling shows different effects of indomethacin at different time points. 38 These in vitro findings need further study to clarify the relationship between length of exposure to NSAID and the ability of cells to recover from the insult.…”
Section: Discussionmentioning
confidence: 99%
“…It would appear that in fracture healing an alternative analgesic is preferable where an increase in osteoblast numbers is important. 38 Probably at one to two weeks post- fracture their use is acceptable and could even be desirable at stages where optimisation of ALP activity is important, e.g. during matrix synthesis and mineralisation of callus.…”
Section: Discussionmentioning
confidence: 99%
“…Nonsteroidal anti-inflammatory drugs (NSAIDs): NSAIDs work by blocking the enzyme cyclooxygenase, which is essential for the production of prostaglandins (Pgs) from the arachidonic acid [68,69].…”
Section: Anti-inflammatory Agentsmentioning
confidence: 99%
“…It is utilised in the treatment of diseases such as osteoarthritis, rheumatic arthritis (Sadowski and Steinmeyer, 2001), gout, cancer and in the prevention of cardiovascular diseases and gynaecologic diseases (Pai et al, 2001) and also used to alleviate the pain after damage or surgery in the tendons and ligaments (Riley et al, 2001). According to some studies (Collier and Ghosh, 1991;Leroux and Saffar, 1993;Guez et al, 2001;Pai et al, 2001;Riley et al, 2001;Forslund et al, 2003;Cohen et al, 2006;Azoubel et al, 2007) indomethacin can interfere in the restoration of the tissue of many organisms, since it inhibits the action of the ciclooxygenase enzyme and consequently the conversion of arachidonic acid into prostaglandin, elements that perform important functions in cell protection, growth, angiogenesis and extracellular matrix production (Savla et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Guez et al (2001) analysed the action of indomethacin in a model of bone remodelling in rats and showed that the drug affected various stages of this remodelling sequence like bone resorption and formation. Several studies have shown the influence of indomethacin in the synthesis of the extracellular matrix of connective tissue (Arumugham and Bose, 1981;Riley et al, 2001).…”
Section: Introductionmentioning
confidence: 99%